Real-time polarization state measurement based on a birefringent crystal wedge. Issue 21 (29th November 2016) - Ma, Jing; Pei, Liyan; Xu, Canhua; Yao, Yangguang
Abstract: We present a method of single-shot polarization state measurement based on a birefringent crystal wedge. The phase delay and amplitude angle of detected light are encoded into two groups of fringes through the interference in a crystal wedge and further decoded by fringe position locations. This method has the merit of real-time measurement, a compact set-up and simple calibration. The principle, set-up, calibration and error analysis are presented in details. In the end, a single-shot measurement set-up with 80 kHz temporal resolution is demonstrated to investigate the molecule dynamic behaviour in a TN liquid crystal under a rectangular voltage.